An inter-city input-output database distinguishing firm ownership in the Greater China area during 2002–2017 - Yafei Wang; Dingyi Xu; Heran Zheng; Ming Ye; Meichen Zhang; Qi He; Kun Cai; Dabo Guan; Shantong Li; Hong Ma; Bo Meng; Zhi Wang; et al. (Scientific Data)
Abstract Most multi-region input-output (MRIO) tables in China focus on provinces or urban agglomerations and ignore the tremendous geographical heterogeneities of economic activities across Chinese prefectural cities, where regional economic centres are usually located for domestic and global production. This paper constructs an inter-city input-output (IO) database with 42 sectors in the Greater China area. Compared with previous MRIO tables, it has three important features: (1) A complete coverage of Chinese cities, including 335 prefectural cities, four municipalities, and Hong Kong, Macao, and Taiwan; (2) Distinguishes three types of firm ownership for every city and sector for four benchmark years; (3) A novel data completion approach to reconcile all accessible micro-level data with city and provincial-level aggregate statistics, and effectively combining the bottom-up and top-down methods commonly used in the MRIO compilation literature. The database can be used in a diverse range of socioeconomic and interdisciplinary issues in the Greater China area at the city level. It also sheds light on other large economies to develop their own inter-city IO tables.